PENGARUH PENGGUNAAN MEDIA BAAMBOOZLE PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Sarah Faradillah; Destri Astrianingsih; Vivit Nurhikmah Havita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this study is to evaluate students' critical thinking skills using Baamboozle as a learning medium on the topic of biodiversity. The research employed a One-Group Pretest-Posttest Design within a pre-experimental model, conducted in a single class. A total of 35 fifth-grade students participated in the study. Data were collected through critical thinking tests administered as pretests and posttests. The data were analyzed using a paired sample t-test with the help of SPSS. The results indicate a significant difference between the pretest and posttest scores after the implementation of Baamboozle in the learning process. These findings demonstrate that Baamboozle effectively enhances students' critical thinking skills. Therefore, Baamboozle can be considered an innovative and engaging learning medium to support the development of critical thinking skills among elementary school students.